Insights into regulatory mechanisms of the NIK-mediated antiviral defense: new components and the molecular bases of the defense - Machado, João Paulo Batista (2015)
The NSP-interacting kinase (NIK) protein, identified through interaction with the geminivirus nuclear shuttle protein (NSP), displays structural, biochemical and biological characteristics consistent with an authentic receptor kinase involved in defense response against geminivirus infection. The activation of this immune receptor leads to phosphorilation of the ribosomal protein L10 (RPL10) and in the subsequent nuclear relocation of this ribosomal protein. Apart from the identification of RPL10 as a downtream component of the defense signaling, others molecular connections that link the NIK activation to the antiviral response, as well as the nature of this defense mechanism, remain to be determined. In this investigation, a new downstream effector component of the NIK-mediated signaling pathway, a transcription fator designated LIMYB (L10-Interacting Myb domain-containing protein), was identified by its capacity to interact with RPL10 through yeast two-hybrid system. Co-immunoprecipitation and bimolecular fluorescence complementation assays showed that RPL10-LIMYB complex occurs stably in the plant, specifically in the nucleus of plant cells. Functional characterization studies showed that LIMYB acts as an authentic transcription fator, binding to and inhibiting expression of ribosomal protein promoters. These results suggest that NIK-mediated antiviral defense mechanism is based on host translation suppression. To examine this hypothesis, the translation levels in tomato lines overexpressing the constitutively active mutant of AtNIK1 (T474D) was initially assessed. The results demonstrated that transgenic lines had lower accumulation of newly synthesized proteins when comparated to WT plants. Subsequently, T474D-overexpressing tomato lines were infected with two highly divergent begomovirus species, ToYSV (Tomato yellow spot virus) and ToSRV (Tomato severe rugose virus). The transgenic lines either displayed attenuated symptons or were asymptomatic. These findings were associated with delay in viral infections, lower infection rates and reduction in viral DNA accumulation in systemically infected leaves. Despite the tolerance phenotype and lower rates of protein synthesis displayed by T474D-overexpressing lines, no difference in the development, physiological performance and horticultural traits was observed between T474D-overexpressing and WT or AtNIK1-overexpressing lines. Finally, whether the reduction in overall levels of host translation caused by overexpression of T474D could affect the viral proteins synthesis was examined. For this purpose, polysomal fractions were isolated from WT and T474D lines infected with ToYSV and examined for the presence of viral mRNA. The results showed lower association of mRNA encoding viral capsid protein at the polysomes fractions of T474D lines when comparated to that of untransformed lines. Collectively, these results indicate that begomovirus are not able to maintain high levels of viral mRNA translation into T474D-overexpressing lines, indicating that the global suppression of the protein synthesis identified in these genotypes may efficiently protect cells against infection by these virus. However, studies of global changes in gene expression of nik1 null alleles revealed that loss of NIK1 function promoted induction of components of the main brassinosteroid signaling hub and of hubs involved in salicylic acid signaling and antibacterial immunity. These results suggest that NIK1 may function as a negative regulator in development and immunity signaling pathways, despite its antiviral property.